Influence of the copepod Mesocyclops longisetus (Crustacea: Cyclopidae) on the survival of Vibrio cholerae O1 in fresh water Influência do copépode Mesocyclops longisetus (Crustacea: Cyclopidae) na sobrevivência de Vibrio cholerae O1 em água doce - Daniela Bastos Araújo; Suzana Cláudia Silveira Martins; Laurênia Maria Braga de Albuquerque; Ernesto Hofer (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 1996)
In an experimental microcosm, an analysis was performed of the influence exerted by freshwater Mesocyclops longisetus copepods on the survival of Vibrio cholerae O1 serovar Inaba. In the State of Ceará, copepods are used in the control of Aedes aegypti larvae. The system consisted of water with a salinity of 0.27‰ and pH 7.5, which after sterilizing filtration was distributed into seven flasks with a volume of 400 ml; in each of six flasks, 10 live copepods were inoculated along with 1 ml of an 8-hour culture of Vibrio cholerae O1 at 37ºC in Alkaline Peptone Water, resulting in a concentration of 3.80x10(4) colony-forming units. The control flask contained only the water with the same bacterial suspension. The system was maintained for six days at room temperature (25-28ºC), and daily duplicate counts were performed in TCBS Agar. Results confirmed a clear association between Vibrio cholerae O1 and the live copepods, based on survival of the bacteria at compatible levels with the initial inoculation until the sixth day of the analysis. Foi analisada num microcosmo experimental a influência exercida por copépodes de água doce da espécie Mesocyclops longisetus na sobrevivência de V. cholerae O1 sorovar Inaba. Os copépodes são utilizados no controle de larvas de Aedes aegypti no Estado do Ceará. O sistema estava constituído de água com salinidade de 0,27‰ e pH 7,5, que após filtração esterilizante foi distribuída em sete frascos em volumes de 400 ml, sendo que em cada um dos seis frascos foram inoculados dez copépodes vivos e 1 ml de uma cultura de oito horas a 37ºC em água peptonada alcalina (pH 8,5) de V. cholerae O1, resultando uma concentração de 3,80x10(4) unidades formadoras de colônias. O controle continha apenas a água com a mesma suspensão bacteriana. O sistema foi mantido durante seis dias à temperatura ambiente (25 28ºC) e, diariamente, foram realizadas as contagens em duplicata em Ágar TCBS. Os resultados evidenciaram uma nítida associação de V. cholerae com os copépodes vivos, através da sobrevivência bacteriana em níveis compatíveis com o inóculo inicial até o sexto dia da análise.